Review of Translation of Šahrestānīhā ī ērānšahr, A Middle Persian Text on Late Antique Geography, Epic and History in Persian - Shima Jaafari Dehaghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Šahrestānīhā ī ērānšahr is a Middle Persian treatise about the historical geography of Sasanian cities in Iran. So far, this treatise has been translated and published in Persian by Hedayat, Oriyan, Taffazoli, and Daryaee. In 2002, Daryaee published this text with Persian and English translation, and in 2009, Jalilian translated Daryaee’s book into Persian. In the present study, we examined Jalilian’s translation of this treatise. It is noteworthy that Jalilian mentioned in his book that the translation of the Middle Persian text is from Daryaee himself. To make the review more accurate and to compare it with other translations, Daryaee and Taffazoli’s translations are cited and compared. First, the transliteration of each sentence is mentioned, and then the translation is written in chronological order. Then, the review of the translations is mentioned. It can be concluded that each of the translations of Middle Persian texts into Persian has new points that, in turn, will help us to better understand Middle Persian texts and ancient Iranian thought.